Thromboelastometric detection of clotting Factor XIII deficiency in cardiac surgery patients. Issue 6 (21st August 2013) - Grossmann, E.; Akyol, D.; Eder, L.; Hofmann, B.; Haneya, A.; Graf, B. M.; Bucher, M.; Raspé, C.
SUMMARY Aim(s) In this article, we aimed to investigate plasma Factor XIII levels after extracorporeal circulation in cardiac surgery by thromboelastometric detection, as extracorporeal circulation causes various coagulation disorders due to the exposure of blood to artificial surfaces, inflammatory induction and mechanical destruction of platelets and coagulation factors, which may particularly affect factors with long half‐lives, such as Factor XIII. Background Since transfusion algorithms are often empirical and laboratory analysis of Factor XIII plasma levels may not be available 24 h a day, bed‐side testing using rotational thromboelastometry (ROTEM) could offer a splendid option to define the cause of excessive peri‐operative bleeding disorders in general and Factor XIII levels in particular in a timely manner and thus facilitating exact substitution therapy. Methods In this trial, we investigated 25 cardiac surgery patients with extracorporeal bypass times over 100 min. Standard laboratory and ROTEM analyses were performed post‐operatively at the time of intensive care unit admission and 6 h later. We implemented EXTEM with additional Factor XIII (teenTEM) as additional test by adding 0·625 IU Factor XIII to standard EXTEM reagents. Results In this observational study, we could not demonstrate a correlation between Factor XIII and MCFEXTEM, CFTEXTEM or MLEXTEM. Neither Factor XIII plasma levels nor MCFEXTEM could predict blood loss. In accordance with previous findings, we were able to demonstrate increased maximum clot firmness (MCF), decreased clot formation time and decreased maximum lysis by adding Factor XIII in vitro (teenTEM vs EXTEM) indicating an improvement in the coagulation process. As shown before, we also found a strong correlation between MCF and platelet and fibrinogen plasma levels. Conclusion In summary, 'teenTEM' test does not seem to detect Factor XIII deficient patients in cardiac surgery. Furthermore, post‐operative blood loss could not be predicted neither by ROTEM nor by laboratory analysis of Factor XIII. In vitro administration of Factor XIII appears to improve laboratory measures of haemostasis.